A study on life cycle cost (LCC) analysis of rigid pavement maintenance and rehabilitation in the Malaysian construction industry - Siti Zulaiha Ahmad Jasmi (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2019)
Life Cycle Cost (LCC) analysis has been recognized as one of the emerging methodologies in cost estimation that can evaluate and compares the cost-effectiveness of different rigid pavement maintenance and rehabilitation alternatives throughout its service lifespan. However, the main drawback of LCC implementation resides with the inferior acquisition of quality cost data inputs (i.e. data availability, accessibility, currency and reliability) to produce a comprehensive and reliable LCC output. In relation to rigid pavement maintenance and rehabilitation in the Malaysian construction industry, the objectives of this research are; i) to identify the most appropriate mathematical cost model that can be applied in the LCC analysis, ii) to assess the quality of cost data inputs with regard to its availability, accessibility, currency and reliability that can be used for LCC analysis, and iii) to evaluate the most appropriate strategies that can be carried out to improve the quality of cost data inputs for LCC analysis. In order to answer the research objectives, qualitative research strategy was adopted, which face-to-face interview was carried out with the respondents who have skills, knowledge or experience in the LCC analysis, or rigid pavement maintenance and rehabilitation works to get their opinions on the subject matter. The literature review also was adopted in this research to study the background of the research and to construct the interview questionnaire. The findings of this research established that the Net Present Value (NPV) is the most appropriate mathematical cost model to be used for LCC analysis of rigid pavement maintenance and rehabilitation. Nevertheless, this research also presents that the cost data inputs for LCC analysis are not ready and quality enough to be used for LCC analysis of rigid pavement maintenance and rehabilitation in the Malaysian construction industry. Thus, this research presents strategies that are considered very appropriate to be proposed in facilitating the cost estimators to elevate the quality of the cost data inputs for LCC analysis, which are; i) the responsible organizations (i.e., PWD, CIDB, MHA, etc.) and educational institution can do research collaborations to improve the LCC applications and the quality of cost data inputs to be used for LCC analysis of rigid pavement maintenance and rehabilitation, ii) there is also need for establishment of LCC specific team in the field of LCC analysis of rigid pavement maintenance and rehabilitation, and iii) the responsible organizations can impose every private agency and concessionaires to submit a well-organized data in order to develop a centralized database for LCC analysis of rigid pavement maintenance and rehabilitation in the Malaysian construction industry.